Application Of The COPRAS Method In Selecting The Best Boarding House For Students - Chairina Sakinah Sitorus; Nanda Afira (PERFECT: Journal of Smart Algorithms, 2026)
Selecting a boarding house is an important decision for students, especially those who come from outside the area and require a comfortable, safe, and suitable place to live. The large number of boarding house options with varying facilities and rental prices often makes it difficult for students to determine the best choice. Therefore, a decision support system is needed to assist the selection process objectively and effectively. This study aims to implement the Complex Proportional Assessment (COPRAS) method in selecting the best boarding house for students based on several predetermined criteria. The criteria used in this study include rental price, distance to campus, facilities, and security. The COPRAS method was chosen because it is capable of evaluating both benefit and cost criteria proportionally. The results of the study indicate that the COPRAS method can rank boarding house alternatives based on their priority values. Based on the calculation results, Alternative A1 (Kost M & U) was identified as the best boarding house with the highest priority value compared to the other alternatives. Therefore, the implementation of the COPRAS method can help students determine boarding house choices that best match their needs and preferences in a faster, more accurate, and objective manner